Predstave trenerjev mladih atletov o pomembnih značilnostih trenerja in učinkovitih trenerskih vedenjih - Železnik Mežan, Lea (Psihološka obzorja (Ljubljana), 2023)
Coach and his behaviour have a huge influence on children in the most sensitive periods of their growth and maturation. Quality of child`s physical, cognitive, social, psychological and emotional development depends on coach`s behaviour. Purpose of this research was to define the character of Slovenian young athletes’ coach on the evidence of his personal qualities and effective coaching behaviours, which enable children to enjoy safe sport activities. Eight young track and field athletes` coaches were interviewed over Zoom, using semi structured interview. They were answering four sets of questions which relate to their young athletes, aged between 9 and 11 years. Content of the interviews was transcribed verbatim and analysed using qualitative content analysis. Thoughts were firstly open coded and then combined into categories which we described. We confirmed the importance of coach`s character and qualities, such as kindness, honesty, warmth etc. According to opinions of Slovenian track and field athletes` coaches, coach`s character is a key factor of the quality of coach-athlete relationship. Even though track and field athletics is an individual sport, coaches emphasize importance of group, friendships, mutual help and respect. Although coach has an important role, especially during child`s maturation, the influence of peers on group cohesion, self-confidence and motivation is also vital. The most important motive for which children are doing sports is pleasure. For this reason, coaches should be stressing task orientation through selfcomparison, progress, learning and endeavouring.
Keywords: children; coaches; interpersonal relationships; medosebni odnosi; motivacija; motivation; osebnostne lastnosti; otroci; personality traits; trenerji